2021
DOI: 10.2991/absr.k.210609.058
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal (Pb) in the Rhizophora apiculata Mangrove in Asahan, North Sumatera, Indonesia

Abstract: Mangroves have an ability in environmental conditions, i.e., in the sediment, and organs. This research was carried out to assess the Pb absorption rate (sediment and mangrove parts of R. apiculata) in the eastern coast of Asahan, North Sumatra. The results showed that Pb content increased in the sediment, but it significantly decreased in leaves. The highest Pb content was in the sediment > roots > fruits > stem bark > leaves. The PCA results of factor loading showed that in the sediment (0.98), roots (0.98),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…These results are in accordance with research, that the heavy metal Pb is absorbed in the roots of Rhizophora compared to other parts [21]. Then, explained that the correlation between heavy metal accumulation between sediments and roots is directly proportional, that is, the higher the concentration of heavy metals in the sediment, the better the accumulation by mangrove roots [6].…”
Section: Concentration Of Heavy Metals Pb and Cu In Sedimentssupporting
confidence: 90%
See 1 more Smart Citation
“…These results are in accordance with research, that the heavy metal Pb is absorbed in the roots of Rhizophora compared to other parts [21]. Then, explained that the correlation between heavy metal accumulation between sediments and roots is directly proportional, that is, the higher the concentration of heavy metals in the sediment, the better the accumulation by mangrove roots [6].…”
Section: Concentration Of Heavy Metals Pb and Cu In Sedimentssupporting
confidence: 90%
“…The ability of mangroves to accumulate heavy metals is different for each species, and the concentration of heavy metals between plant organs is also different for each species. According to stating that the ability to absorb heavy metals in mangroves of the species R. apiculata on the east coast of Asahan, North Sumatra, found that the highest accumulation of heavy metal Pb was in the roots, while the absorption capacity of heavy metal Pb in bark, leaves and fruit was low [6].…”
Section: Introductionmentioning
confidence: 99%
“…Natural mangroves are influenced by various physical and non-physical factors. Physical factors consist of the physicochemical factors and litter dynamics of every month [11], the leaves decomposition over time [12], the supporting element content from mangrove leaves [13], as antioxidant [14] and sequestration carbon and carbon stock [15,16] and as heavy metal absorption [17].…”
Section: Introductionmentioning
confidence: 99%